Торгівля домашньою худобою у волинян: звичаї та повір’я - Пожоджук, Д. (Народна творчість та етнологія, 2018)
У статті розглянуто звичаї та обряди, пов’язані з торгівлею свійськими тваринами. На основі переважно польових етнографічних матеріалів автором з’ясовано основні звичаєво-обрядові особливості купівлі-продажу волинянами домашньої худоби. Зокрема, ідеться про передачу налигача, звичай кидати гроші «на талан» («на щастя»), повір’я та обставини, які впливали на подальше життя придбаної тварини в нового господаря. The submitted article considers customs and rituals related to the trade of domestic animals. Chiefly based on field ethnographic materials, the author finds out the main custom and ritual features of the Volynians’ buying and selling of domestic animals (cows, horses, and pigs). In particular, what is at issue is the transfer of nalyhach (a strap or rope tied up to an animal) while selling livestock, the custom to throw money for luck, beliefs, and circumstances influencing on further well-being of an animal sold.